Peran Komunikasi Dinas Perhubungan Kabupaten Tangerang dalam Menangani Pelanggaran Jam Operasional Angkutan Tanah - Annisa Rufaedah Prastuti; Isniyunisyafna Diah Delima; Riza Gusti rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Judging from the Perbup or Tangerang Regent's regulation Number 12 of 2022 concerning the second amendment to Perbup Number 46 of 2018 concerning restrictions on the operational time for goods cars on roads in the Tangerang Regency area, namely that the operational time for goods transport vehicles (sand, stone, soil) is limited to 22.00 WIB until 05.00 WIB. However, transportation such as trucks carrying mounds of earth that are material for the construction process often violate operating hours. In running the transportation and freight system, such as land-laden trucks in Tangerang Regency, the Transportation Department plays an important role in organizing and managing transportation systems. The method used in this research is a qualitative research method. The communication used by the Tangerang Regency Transportation Service is verbal, through the media, and symbolic communication. In terms of four important implications in Social Systems Theory, such as interdependence, openness, forms of analysis, and organizational adjustments or updates, the communication role of the Tangerang Regency Transportation Service in dealing with violations of land transportation operating hours has carried out these four important implications. This is appropriate and relevant to the Social Systems Theory used in this research.